2006
DOI: 10.1136/hrt.2006.109736
|View full text |Cite
|
Sign up to set email alerts
|

Neopterin is associated with plaque inflammation and destabilisation in human coronary atherosclerotic lesions

Abstract: Neopterin can be considered as one of the significant factors in the process of plaque inflammation and destabilisation in human coronary atherosclerotic lesions. Its exact role in the process needs to be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 26 publications
3
33
0
1
Order By: Relevance
“…Moreover, our previous study demonstrated that infiltration of myeloperoxidase (MPO), a strong prooxidant enzyme released from activated neutrophils, occurs in the culprit lesions of patients with UAP 28) . In our immunohistochemical analysis to detect neopterin in coronary atherectomy specimens 11) , the neopterin-positive macrophage score showed a significant positive correlation with the number of MPO-positive neutrophils. In addition, it has been shown that the reaction generating neopterin from 7,8-dihydroneopterin is oxidation by HOCl, mainly produced by MPO from neutrophils 3,20) .…”
Section: Neopterin and Plaque Instability In Coronary Arteriesmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, our previous study demonstrated that infiltration of myeloperoxidase (MPO), a strong prooxidant enzyme released from activated neutrophils, occurs in the culprit lesions of patients with UAP 28) . In our immunohistochemical analysis to detect neopterin in coronary atherectomy specimens 11) , the neopterin-positive macrophage score showed a significant positive correlation with the number of MPO-positive neutrophils. In addition, it has been shown that the reaction generating neopterin from 7,8-dihydroneopterin is oxidation by HOCl, mainly produced by MPO from neutrophils 3,20) .…”
Section: Neopterin and Plaque Instability In Coronary Arteriesmentioning
confidence: 99%
“…Circulating levels of neopterin have been reported to be higher in patients with acute coronary syndrome (ACS) than in control subjects and in patients with stable angina pectoris (SAP) 6,7) . Furthermore, recent studies have shown a direct association between neopterin and plaque instability in coronary arteries [8][9][10][11] ( Table 1). Several coronary angiographic studies have shown a relationship between increased neopterin levels and complex coronary lesions in patients with unstable angina pectoris (UAP) 8,9) ; however, neopterin levels did not correlate with the number of diseased coronary vessels, suggesting that neopterin may be a marker of inflammatory CAD activity rather than a measure of the anatomical extent of the coronary atheromatous process 8,9) .…”
Section: Neopterin and Plaque Instability In Coronary Arteriesmentioning
confidence: 99%
See 3 more Smart Citations